Efektivitas Terapi Musik Klasik dalam Mengatasi Stres Akademik: Tinjauan Literatur: Penelitian - Marssel Michael Sengkey; Eka Prasetyo Ningsih; Yesa Mokoginta; Sheryn Eglecia Karamoy (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Academic stress is a common issue frequently experienced by both school and university students. This condition is typically triggered by various academic demands, such as heavy workloads, examination schedules, and pressure to achieve high performance. This literature review aims to examine the effectiveness of classical music therapy as a non-pharmacological intervention for reducing academic stress. Based on an analysis of eight research journals, classical music therapy has been shown to significantly reduce stress levels among students at various educational levels. For example, a study by Cahyani et al. (2024) demonstrated that the combination of natural sound music and progressive muscle relaxation effectively reduced stress in final-year university students (p=0.012). Literature reviews by Yuliana et al. (2023) and Febrianti et al. (2023) reported that classical music, particularly Mozart’s compositions, stimulates alpha and beta brain waves and regulates stress hormones such as ACTH, showing significant results after 20-minute sessions over a two-month period. Seprian et al. (2023) also found that instrumental music at 432 Hz effectively reduced academic stress in nursing students (p=0.000). Overall, despite variations in music types, classical music consistently demonstrates positive psychological and physiological effects. Therefore, classical music is considered an effective, accessible intervention and is recommended for further research to strengthen empirical evidence.